TRENDS IN THE DEVELOPMENT OF MARKETING COMMUNICATIONS IN THE GLOBAL INTERACTIVE SPACE - N. Kochkina (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article identifies trends in the development of marketing communications in the global interactive space by analyzing the factors of their functioning and researching motivation of viral audience. It is revealed the prevalence of interactive technologies in today's information space and the growth dynamics of interactive advertising market. It is proved that favorable conditions for marketing communications' functioning forms the basis for the development of viral advertising as an effective communication tool for untraditional impact on potential customers. The popularity of social networks as a major source of viral messages is determined. The motivation of YouTube audience, which provides a resonant video viewing and retransmission, is investigated. Gender and age differences that stipulate communication affect on consumers are identified. Cyclic social consciousness is observed that demands further research of viral audience, including constructing scenarios of viral behavior.